Participatory Critical Incident Technique: A Participatory Action Research Approach for Counselling Psychology - Chou, Fred; Kwee, Janelle; Buchanan, Marla; Lees, Robert (Canadian Journal of Counselling and Psychotherapy, 2016)
This article provides an overview of the utilization of the participatory critical incident technique (PaCIT), an approach that incorporates participatory action research (PAR) with the critical incident technique (CIT). This method fits with the aims of counselling psychology to bring social justice and action into the forefront of research activities (Canadian Psychological Association, 2009; Kennedy & Arthur, 2014). PaCIT addresses potential limitations of both methods and is a viable research tool for use with marginalized groups and within cross-cultural contexts. Based on a recently completed project with youth in alternative education, we present a theoretical and practical approach for integrating CIT within a PAR framework.